Care Providers’ Perspectives on Disrespect and Abuse of Women During Facility-Based Childbirth in Ethiopia: A Qualitative Study - Mehretie Adinew Y; Kelly J; Marshall A; Smith M (Dove Medical Press, 2021)
Yohannes Mehretie Adinew,1,2 Janet Kelly,1,* Amy Marshall,3,* Morgan Smith1,* 1Adelaide Nursing School, The University of Adelaide, Adelaide, Australia; 2College of Health Sciences and Medicine, Wolaita Sodo University, Sodo, Ethiopia; 3College of Nursing and Health Sciences, Flinders University, Adelaide, Australia*These authors contributed equally to this workCorrespondence: Yohannes Mehretie Adinew Tel +251 91-202-1605Email yohannes.adinew@adelaide.edu.auBackground: It is increasingly evident that disrespect and abuse of women during facility-based childbirth is a violation of a woman's rights and a deterrent to the use of life-saving maternity care. Understanding care providers' perspectives of disrespect and abuse during facility-based childbirth is an essential element to aid in fully comprehending the problem and its underlying complexities.Objective: To explore care providers' perspectives of disrespect and abuse during facility-based childbirth.Methods: This study used a qualitative descriptive design involving fifteen in-depth, semi-structured, interviews conducted between 5 October 2019 and 25 January 2020 in north Showa zone of Oromia region, central Ethiopia. Purposive sampling enabled health care professionals working in maternity units of health facilities who have direct involvement in care of women during pregnancy and labor to be recruited. Thematic analysis using Open Code software was used to explore the perspectives of participants.Results: Four themes were identified. 1) Disrespect and abuse breaches professional standards, 2) Disrespectful and abusive actions are justified at times to save the mother and her baby, 3) Disrespect and abuse is used as a tool to assert power, and 4) Disrespect and abuse arise from health system deficiencies.Conclusion: Disrespect and abuse is triggered by underlying beliefs about risk versus care, provider attitudes, stress and burnout, and health service structural issues including a lack of medicines and supplies. A number of strategies could improve the quality of maternity care, including training providers how to manage difficult and complex situations, addressing root causes of disrespect and abuse, and increasing access to resources.Keywords: health care workers, disrespect, human rights abuses, respect, birthing centers, Ethiopia